2006
DOI: 10.1248/yakushi.kj00004483555
|View full text |Cite
|
Sign up to set email alerts
|

α_1-Adrenoceptor Subtype Selectivity and Organ Specificity of Silodosin (KMD-3213)

Abstract: The selectivity of silodosin (KMD − 3213), an antagonist of or1− adrenoceptor (AR) , to the subtypes (α 且 A − , α IB − and α ID − ARs)was examined by a receptor − binding study and a functional pharmacological study , and we compared its sub − type − selectivity With those of other α 1 − AR antagonjsts . In the receptor − binding study , a replacement experiment using [ 3H ] − prazosin was conducted using the membrane fraction of mouse − derived LM (tk −)cells in which each of three hu − man ai − AR subtypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…␣ 1D -Adrenoceptor predominantly mediates NA-induced contraction of the rat thoracic aorta (Marucci et al 2005). In contrast to the rat thoracic aorta, ␣ 1A -adrenoceptor is the predominant subtype expressed in the rabbit prostate, which is responsible for the NA-induced contractile responses (Tatemichi et al 2006). In the isolated rabbit prostate preparations used in this study, we further found that the concentration-contraction curves for PHE were inhibited by (-)DOX, (ϩ)DOX, and (Ϯ)DOX in a competitive manner, and there were no signifi- -29.4Ϯ7.72)** Note: *, P Ͻ 0.05 and **, P Ͻ0.01 compared with the solvent control; # , P Ͻ 0.05 and ## , P Ͻ 0.01 compared with preparation before drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣ 1D -Adrenoceptor predominantly mediates NA-induced contraction of the rat thoracic aorta (Marucci et al 2005). In contrast to the rat thoracic aorta, ␣ 1A -adrenoceptor is the predominant subtype expressed in the rabbit prostate, which is responsible for the NA-induced contractile responses (Tatemichi et al 2006). In the isolated rabbit prostate preparations used in this study, we further found that the concentration-contraction curves for PHE were inhibited by (-)DOX, (ϩ)DOX, and (Ϯ)DOX in a competitive manner, and there were no signifi- -29.4Ϯ7.72)** Note: *, P Ͻ 0.05 and **, P Ͻ0.01 compared with the solvent control; # , P Ͻ 0.05 and ## , P Ͻ 0.01 compared with preparation before drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we speculate that a chiral carbon atom in the molecular structure of doxazosin does not affect its activity at the therapeutic target of ␣ 1A -adrenoceptors in the prostate, but significantly changes its blocking activity against vasculature ␣ 1A -adrenoceptors and its inotropic effects in the heart tissues via an ␣ 1 -adrenoceptorindependent mechanism. Therefore, the first step of this study was to determine the pA 2 (or pK B ) values for (ϩ)DOX and (-)DOX using 2 classical and widely used in-vitro models for ␣ 1 -adrenoceptor subtypes, which is the rabbit prostate preparation (Tatemichi et al 2006) for ␣ 1A -adrenoceptors, and the rat thoracic aorta preparation (Marucci et al 2005) for ␣ 1D -adrenoceptors. Then, the inotropic and chronotropic effects of high concentrations of (ϩ)DOX and (-)DOX were analyzed in isolated heart preparations.…”
Section: Introductionmentioning
confidence: 99%
“…2), used clinically as a second generation therapeutic agent, has been reported to present a better uroselectivity profile due to its relatively higher affinity for alpha 1A and 1D subtypes [17]. However, its selectivity is modest and therefore is directly dependent on the therapeutic dosage (0.4 mg/day) ensuring the right balance between efficacy and safety [17e19].…”
Section: Introductionmentioning
confidence: 99%
“…[29] In vitro studies showed that silodosin's alpha-1a: Alpha-1b binding ratio is in the order of 160:1. [29] Clinically, this has resulted in rapid and sustained efficacy, increased flow rates as well as improvements in quality of life scores, which are broadly comparable to tamsulosin.…”
Section: Methodsmentioning
confidence: 99%
“…[29] In vitro studies showed that silodosin's alpha-1a: Alpha-1b binding ratio is in the order of 160:1. [29] Clinically, this has resulted in rapid and sustained efficacy, increased flow rates as well as improvements in quality of life scores, which are broadly comparable to tamsulosin. [3031] Silodosin was found to have minimal risk of cardiovascular effects although it did have a greater risk of ejaculatory dysfunction than tamsulosin in direct comparisons, 14.2 to 22.3% versus 1.6-2.1%, respectively.…”
Section: Methodsmentioning
confidence: 99%